2023
DOI: 10.3390/microorganisms11010123
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into Goat Cheese: The Tales of Artisanal and Industrial Gidotyri Microbiota

Abstract: The purpose of this study was to determine for the first time the microbiota in artisanal-type and industrial-type Gidotyri cheeses and investigate the influence of the cheese-making practices on their composition using culture-independent techniques. The microbiota present in artisanal with commercial starters (Artisanal_CS, n = 15), artisanal with in-house starters (Artisanal_IHS, n = 10) and industrial (Ind., n = 9) Gidotyri cheese samples were analyzed using a targeted metagenomic approach (16S rRNA gene).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…However, their absence has also been reported [28,45,59,69], indicating that these products can be made without their contribution. This seems also to be the case with dairy products [115][116][117].…”
Section: The Concept Of Native Food Microbiotamentioning
confidence: 77%
See 1 more Smart Citation
“…However, their absence has also been reported [28,45,59,69], indicating that these products can be made without their contribution. This seems also to be the case with dairy products [115][116][117].…”
Section: The Concept Of Native Food Microbiotamentioning
confidence: 77%
“…However, their absence has also been reported [28,45,59,69], indicating that these products can be made without their contribution. This seems also to be the case with dairy products [115][116][117]. The concept of the microbiome and the distinction between the microorganisms that participate in core and occasional ones also exist in the case of the spoilage microbiota.…”
Section: The Concept Of Native Food Microbiotamentioning
confidence: 93%
“…Additional virulence STR genes ( asa1, mrp, sly, bay, bca, speG, scpB, ssa ) were tested for the S. bovis/equinus complex and S. lutetiensis in particular ( Chen et al., 2021 ; Özkan et al., 2021b ); whereas the virulence genes ( sua, pauA, skc, gapC, hasC ) of the S. uberis/parauberis group ( Zhang et al., 2020 ) differ from the Enterococcus -specific virulence genes tested in this study. To our knowledge, no previous culture-dependent studies have reported the presence/prevalence of S. parauberis isolates in Greek raw milk or traditional cheese; however, a recent targeted (16S rRNA) metagenomic study reported the prevalence of S. parauberis (OTU 50) in the microbiota of artisanal Gidotyri cheese ( Nelli et al., 2023 ). Therefore, further studies are needed to assess the biochemical characteristics and virulence potential, as well as the antibiotic resistance, of the present S. parauberis isolates from RM.…”
Section: Resultsmentioning
confidence: 99%
“…thermophilus, and Lb. delbrueckii as the three most prevailing species in white brined cheeses [24,26,27]. Leu.…”
Section: Identification Of Sfela Microbiome At Species Level Using Sh...mentioning
confidence: 99%
“…Both techniques have been previously applied in studies conducted for the characterization of various white brined cheese microbiomes. More specifically, amplicon-based sequencing for the identification of both bacterial and yeasts genera has been employed in the case of various Turkish white cheeses including Tulum and Ezine [24][25][26], Greek artisanal cheeses like Kalathaki Limnou, Gidotyri and Batzos, [27][28][29], Brazilian Minas cheese [30] and the Cypriot cheeses Halloumi and Halitzia [31,32]. Feta, which is the most popular Greek cheese, has been selected as the basis for multiple studies employing amplicon sequencing and/or shotgun metagenomics to explore its microbiome under different technological conditions [33][34][35].…”
Section: Introductionmentioning
confidence: 99%